Theater as Metaphor - Penskaya, Elena; Küpper, Joachim (De Gruyter, 2019)
The papers of the present volume investigate the potential of the metaphor of life as theater for literary, philosophical, juridical and epistemological discourses from the Middle Ages through modernity, and focusing on traditions as manifold as French, Spanish, Italian, German, Russian and Latin-American.